Scientific collaboration network ammong Brazilian universities: an analysis in dentistry area - Escalona-Fernandez, Maria Isabel; Pulgarin-Guerrero, Antonio; Oliveira, Ely Francina Tannuri de; Gracio, Maria Cláudia Cabrini (Faculdade de Filosofia e Ciências, 2013)
This paper analyses the scientific collaboration network formed by the Brazilian universities that investigate in dentistry area. The constructed network is based on the published documents in the Scopus (Elsevier) database covering a period of 10 (ten) years. It is used social network analysis as the best methodological approach to visualize the capacity for collaboration, dissemination and transmission of new knowledge among universities. Cohesion and density of the collaboration network is analyzed, as well as the centrality of the universities as key-actors and the occurrence of subgroups within the network. Data were analyzed using the software UCINET and NetDraw. The number of documents published by each university was used as an indicator of its scientific production.